Experience of maintaining tooth brushing for children born with a cleft lip and/or palate - Yin-Ling Lin; Karen Davies; Peter Callery (BMC, 2017)
Abstract Background Children with a Cleft Lip and/or Palate (CL/P) have been reported to have poorer oral health than those without the condition. The consequences for these children can be particularly problematic due to implications for future treatments. Tooth brushing is an important behaviour contributing to children's oral health, but is under researched in the CL/P population. The aim of the study is to explore the experience of maintaining tooth brushing among children in the United Kingdom (UK) with a CL/P and their parents. Methods Semi-structured interviews were carried out with twenty-two parents and sixteen children with a CL/P (5-11 years), recruited at a cleft centre in the UK. Thematic analysis was used for data analysis. Results Three key themes were drawn from the qualitative data: first, parents of children with a CL/P generally had strong motivation to look after their children's teeth but children's motivation was inconsistent. Second, parents were primary enablers of children's tooth brushing behaviour, often employing approaches adapted to their child's characteristics to encourage tooth brushing. Third, a range of obstacles were encountered by parents and children in maintaining regular tooth brushing behaviours. They reported obstacles such as issues related to CL/P, 'forgetting' and childhood illness. Conclusions The paper suggests that parents of children with a CL/P need support to enact their intention to maintain regular tooth brushing and prioritise tooth brushing within the context of demanding and dynamic family life.